Lichen myxedematosus: a rare group of cutaneous mucinosis - Cárdenas-Gonzalez, Ramiro Eugenio; Ruelas, Maira Elizabeth Herz; Candiani, Jorge Ocampo (Anais brasileiros de dermatología, 2019)
Cutaneous mucinoses are a heterogeneous group of dermatoses in which excess deposition of mucin in the dermis gives the skin a waxy appearance, with papules and plaques that can vary from self-healing mucinosis to even disrupting the normal shape of a patient’s face, conferring a leonine facies, or be part of life threatening diseases like scleromyxedema. This review will describe the most recent classification on lichen myxedematosus in the generalized (scleromyxedema) and the localized forms, as well as the different organ systems involved in scleromyxedema, diagnostic workup, current management, and prognosis.